Evaluation of Renal Cortical Thickness in Hydronephrosis Patients on Ultrasound at Hayatabad Medical Complex Hospital Peshawar - Gul, Huma; Saleem, Khadeeja; Ubaid Ullah,; Noreen, Safia; Ghazal,; Rizwan Ullah, (Indus Journal of Bioscience Research, 2025)
Background: Hydronephrosis is often provoked by a previous medical disease or risk factors such as congenital obstruction, unilateral obstructive uropathy, nephrolithiasis, urinary tract infections, tissue scarring, thrombosis, neuromuscular disorders, malignancy, benign prostatic hyperplasia, and pregnancy. The management of hydronephrosis has evolved significantly due to the frequent use of prenatal ultrasonography. Material and method: This cross-sectional descriptive research was performed at the Radiology Department of Hayatabad Medical Hospital Complex, Peshawar from July to December 2024, using a convenience sample method. Patients were chosen according to inclusion criteria that included all genders and ages referred for renal scans, whereas those with a history of renal surgery, transplantation, or trauma were excluded. Results: The study investigated 233 individuals with acute hydronephrosis using descriptive and inferential statistical techniques to evaluate renal cortical thickness and its correlation with demographic and clinical factors. Notable correlations were identified between weight and hydronephrosis grade (p < 0.05), with weight serving as a vigorous predictor of severity. Age exhibited a significant trend, indicating that older persons were more prone to markedly decreased renal cortical thickness, but statistical significance varied within categories (p = 0.075 for adults aged 41–60 years). Gender and residency exhibited relationships with hydronephrosis grade, although were not statistically significant (p > 0.05). The size of the kidney changed markedly with the severity of hydronephrosis, indicating its increasing effect. Conclusion: The research underscores the considerable influence of weight and age on renal cortical thickness and the severity of hydronephrosis, highlighting their contribution to disease development. These results highlight the need for focused treatments and more research to enhance diagnostic and therapeutic approaches for hydronephrosis.